Application of Arcs Model for Utilizing Blogs to Enhance Learners' Motivation in Higher Education: Naveed Sultana ,Aysha Khalil (PJDOL, 2023)
Social networks are main contributors to enhanced learning and teaching patterns in higher education institutions at global level. Social networking sites establish awareness for the ownership of learning amongst learners. In fact motivation is an important factor in learning regardless of developing educational technologies and emerging online learning approaches. Keller (2000) focuses on the importance of motivation by arguing that accelerating and maintaining the motivation of learners, and coming across valid and reliable motivational methods is a challenge for educators. Keller presented the motivational model called 'ARCS Model' which brings together four motivational factors, having impact on gaining i) Attention of learners, ii) determining the Relevance of teaching to learning styles and learning goals of learner, iii) encouraging Confidence regarding prospects and outcomes of learning, and iv) crafting instructionsatisfactory for the learners.